Aplikasi Pemilihan Penyuluh Pertanian Teladan dengan Metode MPE: Array - Sari, Febrina; anti, Desy; Fitriana, Liza (Universitas Harapan Medan, 2020)
The assessment of the Exemplary Self-Help Agricultural Extension candidates aims to motivate the Self-Help Agricultural Extension agents to improve their performance as civil servant agricultural extension partners in conducting agricultural extension services in rural areas. The assessment is done by filling out an assessment form that involves many criteria, for each criteria it is further divided into several sub criteria. This of course will take quite a long time in the calculation and recapitulation and ranking process if done manually. To solve this problem, a Application was built by implementing the exponential comparison method (MPE). This method is one of the methods of a decision support system whose final result is a ranking. This Application makes it easier for the assessment team to decide on exemplary independent agricultural extension workers, because the Application will provide more accurate, measurable and reliable recapitulation results. The results showed that the agricultural instructor with the initials C was selected as an exemplary self-help agricultural extension with the highest value of 1455